Food pattern and perception of students about food served in municipal schools according to health vulnerability - Gabriela Gomes de Paiva; Luíza Campos Parreira; Eline Martins Viana da Costa; Rosana Maria Calazans; Maitê Costa da Silva; Luana Caroline dos Santos; Simone Cardoso Lisboa Pereira; Bruna Vieira de Lima Costa (Universidade do Estado do Rio de Janeiro, 2021)
Objective: analyze the food pattern and perception of students about the food served in schools, according to health vulnerability. Methods: This is a cross-sectional study, carried out with a representative sample of Elementary School students from the Municipal Network of Belo Horizonte. Health vulnerability was determined by the Health Vulnerability Index (HVI) of the census sectors of schools. Eating habits and perceptions of meals served in the school were collected. Pearson's Chi-squared test was used to determine differences according to the Health Vulnerability Index. Results: 3,557 students were interviewed. Students from schools with less vulnerability had the habit of buying food in stores close to the school (p = 0.01); a smaller proportion of the students perceived the school meals as varied (p <0.001), the eating time as sufficient (p<0.001), and the importance of food served in municipal schools (p=0.02). Conclusion: The food pattern and perception of food varied according to the school's vulnerability. In schools with less vulnerability, students bought more food in the surroundings and showed less acceptance and appreciation of school food. The investigation of socio-economic and environmental factors is warranted to understand the conditions that may influence the adequate supply of school meals to all students.